Employability Characteristics and Their Impact On Social Impact: An Exploratory Study On Women's Small Social Enterprises - Ali Al-Tahitah; Mohammed Ali Al-Awlaqi; Nasser Habtoor; Saib Sallam Thabet; Mohammed Abdulrab; Ishaq Ibrahim (Elsevier, 2024)
Indexed by Scopus